The Application of the Discovery Learning Method in Arabic Language Instruction as an Effort to Improve Student Learning Achievement - Rahmawati Rahmawati; Moh Aman (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2024)
The purpose of this study is to describe the improvement in learning achievement through the Discovery Learning model in Arabic language instruction at Pondok Pesantren Al-Mansyuriyah Sepatan, Tangerang. The method used in this study is Classroom Action Research (CAR). This method comprises four stages: planning, action, observation, and reflection. These four stages are carried out within a single cycle, which is repeated with the same procedures and remains focused on problem solving through self-discovery, self-investigation, and information seeking, using the Discovery Learning model. Based on the research findings, students' learning achievement improved through the Discovery Learning model. This improvement is evident in the learning outcomes for each cycle. In cycle 1, the average pretest score was 68.83, and the average posttest score was 75.5. In cycle 2, the average pretest score was 62.67, and the average posttest score was 89.00. The increase in learning outcomes is also evident from the average N-Gain values for each cycle: 0.22 in cycle 1 and 0.70 in cycle 2. These results demonstrate that the researcher's Discovery Learning model successfully improved students' learning achievement.